2020
DOI: 10.1167/tvst.9.10.11
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes of Macular Curvature in Patients with Retinitis Pigmentosa

Abstract: Purpose To investigate the longitudinal changes of the macular curvature in eyes with retinitis pigmentosa (RP) and to determine the factors associated with the changes. Methods We reviewed the medical charts of 107 RP patients, for whom the axial length of their right eyes ranged from 21.5 to 26.0 mm and who had had been followed by spectral-domain optical coherence tomography (OCT). The OCT images at the initial and the most recent examinations were compared. The mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…However, it remains unclear whether macular staphyloma and changes in the curvature are associated with the progression of retinal degeneration. The reason for the positive correlation between AL and postoperative BCVA found in this study is unclear, but recently, Meinert et al reported that the macular curvature in RP eyes becomes more concave in eyes with preserved EZ width at >2000 μ m [ 19 ]. Further investigations on the relationship between ocular morphology and visual function in RP patients are needed.…”
Section: Discussionmentioning
confidence: 86%
“…However, it remains unclear whether macular staphyloma and changes in the curvature are associated with the progression of retinal degeneration. The reason for the positive correlation between AL and postoperative BCVA found in this study is unclear, but recently, Meinert et al reported that the macular curvature in RP eyes becomes more concave in eyes with preserved EZ width at >2000 μ m [ 19 ]. Further investigations on the relationship between ocular morphology and visual function in RP patients are needed.…”
Section: Discussionmentioning
confidence: 86%
“…It is possibly reported in RP and pathologic myopia. 22 It is speculated to be related to CT, 23 retinal structure, 24 and ellipsoid zone width. 11 The distorted structure may increase the longitudinal tractive force to subfoveal choroid and decrease the CT.…”
Section: Discussionmentioning
confidence: 99%